"The effects of gender transport poverty in Karachi". (April 2020) - Iqbal, Sana; Woodcock, Andree; Osmond, Jane
Abstract: Karachi is the economic hub of Pakistan, with an estimated population of 20 million (Khawar, 2017). However, it lacks a systematised public transport service, with few buses and no trains, leaving private bus owners to run poor-quality deregulated services. Although it may be argued that poor service fails to accommodate the needs of the inhabitants of this megacity, women are additionally marginalised by restricted transport services. Men not only have more space allocated to them on public transport but also have the freedom to use alternative and cheaper private modes of transport such as motorbikes and cycles, which are socially discouraged for women. However, there is little literature on the barriers to women's mobility in countries in the Global South, which shows how they are differentially deprived of their agency owing to the cultural norms and gender disparity in transport provision. This paper aims to identify and assess the various aspects of gender transport poverty faced by young working women in Karachi using a quantitative survey. It will broaden the understanding of gender transport poverty in the Global South.